2012
DOI: 10.1179/1743281211y.0000000045
|View full text |Cite
|
Sign up to set email alerts
|

Liquid metal experiments with swirling flow submerged entry nozzle

Abstract: The influence of a swirling flow inside the submerged entry nozzle on the structure and the stability of a liquid metal flow in a physical model of a slab casting mould are investigated. For visualisation of the flow, contactless inductive flow tomography (CIFT) is applied. As expected and desired, the swirling flow leads to a stronger upward fluid motion along the walls. At the same time, however, the oscillatory character of the flow becomes stronger. These flow features obtained with CIFT are shown to be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…25,26,28,29,31,32) The swirling flow is obtained by installing the electromagnetic stirring equipment outside the SEN. Simulation results 25,29,31,32) showed that it can produce a good swirling flow inside the SEN. However, it requires an equipment cost and an electricity cost.…”
Section: )mentioning
confidence: 99%
“…25,26,28,29,31,32) The swirling flow is obtained by installing the electromagnetic stirring equipment outside the SEN. Simulation results 25,29,31,32) showed that it can produce a good swirling flow inside the SEN. However, it requires an equipment cost and an electricity cost.…”
Section: )mentioning
confidence: 99%
“…[6] A magnetic stirrer consisting of a pair of permanent magnets driven by a motor with a maximum rotation frequency of 50 Hz was mounted around the SEN (Figure 6). Figure 2b shows the position of the stirrer at the Mini-LIMMCAST facility.…”
Section: Stirrer Around the Senmentioning
confidence: 99%
“…Then, we give a summary of the main results of a two-phase flow experiment with the main focus on the tests with high argon flow rates that show several sudden transitions between various flow regimes in the SEN [5] and in the mold. We also present an experiment without argon supply but with an electromagnetic stirrer positioned at the SEN. [6] In the last section, we discuss some new developments towards a robust measurement of the induced magnetic field using a AC measuring field and pickup coils, which will be needed in order to implement the CIFT method within the harsh environment of a real casting machine. Figure 1 shows a schematic sketch of the Mini-LIMMCAST facility that has been built at HZDR as a cold liquid metal model of a continuous slab caster.…”
Section: Introductionmentioning
confidence: 99%
“…The techniques like nail-board measurement, 52,[99][100][101][102] torque measuring technique, 59) inclination angle method, 100) thermocouple inside mold and slab surface measurements, X-ray of melt evaluation, have been used to feel the nerve of the continuous steel caster. Newer techniques like Contactless Inductive Flow Tomography (CIFT) measurement [103][104][105][106] are evolving to get more detailed information inside the mold flow. Slab surface temperature measurement 107) at the start of secondary cooling provides much needed data to validate the solidification model for the plant conditions.…”
Section: Measurement and Validation Aspectmentioning
confidence: 99%